Effect of carbon source on the properties of dense α-SiC. (15th December 2021) - Aygüzer Yaşar, Zeynep; DeLucca, Vincent A; Haber, Richard A
Abstract: Due to its outstanding properties, SiC is a candidate material for use in special applications such as armor. In order to use SiC in these special applications, it is necessary to produce fully dense ceramics. The ability to produce high density materials with superior performance depends on a number of factors. One of these factors is the addition of carbon to aid sintering. In this study, the effect of different carbon sources and ratios on the elastic and mechanical properties of SiC was investigated. Two types of carbon (lamp black and phenolic resin) were added to SiC in different ratios (0%–2% wt.). All samples were sintered via the spark plasma sintering (SPS) method at 1900 °C for 15 min under 50 MPa pressure. Samples made with lamp black were reached full density at 1.0 wt.%C, and the hardness and elastic modulus values were ∼22GPa and 440 GPa, respectively. While samples made with both carbon sources showed similar bulk mechanical properties, the samples made with lamp black showed more consistent microstructures. The carbon from the phonelic resin source did not appear to be as well distributed as that from the lamp black source. The results also confirmed that addition of carbon into SiC was essential to improve the density and other mechanical properties associated with it.